A simplified edge illumination set-up for quantitative phase contrast mammography with synchrotron radiation at clinical doses. (9th January 2015) - Longo, Mariaconcetta; Rigon, Luigi; Lopez, Frances C M; Chen, Rongchang; Dreossi, Diego; Zanconati, Fabrizio; Longo, Renata
Abstract: This work presents the first study of x-ray phase contrast imaging based on a simple implementation of the edge illumination method (EIXPCi) in the field of mammography with synchrotron radiation. A simplified EIXPCi set-up was utilized to study a possible application in mammography at clinical doses. Moreover, through a novel algorithm capable of separating and quantifying absorption and phase perturbations of images acquired in EIXPCi modality, it is possible to extract quantitative information on breast images, allowing an accurate tissue identification. The study was carried out at the SYRMEP beamline of Elettra synchrotron radiation facility (Trieste, Italy), where a mastectomy specimen was investigated with the EIXPCi technique. The sample was exposed at three different energies suitable for mammography with synchrotron radiation in order to test the validity of the novel algorithm in extracting values of linear attenuation coefficients integrated over the sample thickness. It is demonstrated that the quantitative data are in good agreement with the theoretical values of linear attenuation coefficients calculated on the hypothesis of the breast with a given composition. The results are promising and encourage the current efforts to apply the method in mammography with synchrotron radiation.